2018
DOI: 10.1002/2017wr022046
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal Responses of Groundwater Flow and Aquifer‐River Exchanges to Flood Events

Abstract: Rapidly rising river stages induced by flood events lead to considerable river water infiltration into aquifers and carry surface‐borne solutes into hyporheic zones which are widely recognized as an important place for the biogeochemical activity. Existing studies for surface‐groundwater exchanges induced by flood events usually limit to a river‐aquifer cross section that is perpendicular to river channels, and neglect groundwater flow in parallel with river channels. In this study, surface‐groundwater exchang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
41
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(46 citation statements)
references
References 51 publications
5
41
0
Order By: Relevance
“…The results indicate that the linearized solution (20) is very close to the nonlinear solution during the simulated period except that it slightly underestimated the peak values of the hydraulic heads (Figure c). Although both linearization approaches served well, the solution (20) utilizing trueh¯=)(H0+H)(t/2 is closer to the nonlinear solution than that with trueh¯=H0 (Figure c), which is consistent with the results of the previous studies (Guo, ; Liang et al, ; Liang & Zhang, ; Tolikas et al, ; Upadhyaya & Chauhan, ). The increased value of trueh¯ compared to the initial H 0 can be explained physically by the increase of saturated thickness of the aquifer in the stream bank vicinity.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…The results indicate that the linearized solution (20) is very close to the nonlinear solution during the simulated period except that it slightly underestimated the peak values of the hydraulic heads (Figure c). Although both linearization approaches served well, the solution (20) utilizing trueh¯=)(H0+H)(t/2 is closer to the nonlinear solution than that with trueh¯=H0 (Figure c), which is consistent with the results of the previous studies (Guo, ; Liang et al, ; Liang & Zhang, ; Tolikas et al, ; Upadhyaya & Chauhan, ). The increased value of trueh¯ compared to the initial H 0 can be explained physically by the increase of saturated thickness of the aquifer in the stream bank vicinity.…”
Section: Resultssupporting
confidence: 89%
“…Þ =2 is closer to the nonlinear solution than that with h ¼ H 0 (Figure 3c), which is consistent with the results of the previous studies (Guo, 1997;Liang et al, 2018;Liang & Zhang, 2012a;Tolikas et al, 1984;Upadhyaya & Chauhan, 1998). The increased value of h compared to the initial H 0 can be explained physically by the increase of saturated thickness of the aquifer in the stream bank vicinity.…”
Section: Water Resources Researchsupporting
confidence: 90%
“…Field and modeling studies at the transect scale typically study BSE processes at an individual 2-D transect oriented perpendicular to the channel (Chen & Chen, 2003;Doble et al, 2012;Koussis et al, 2007;Rorabaugh, 1963;Squillace, 1996). Few studies have looked at spatial and temporal BSE dynamics from a longitudinal perspective (Liang et al, 2018;Pinder & Sauer, 1971;Xie et al, 2016). Each of these studies evaluated the effect that a flood wave moving down a river corridor has on the spatiotemporal BSE.…”
Section: /2019wr025210mentioning
confidence: 99%
“…While several numerical modeling studies have been applied to specifically investigate surface water‐groundwater interaction during flood events (Whiting and Pomeranets ; Chen et al ; Doble et al ; Doble et al ; Xie et al ; Liang et al ) these studies have not used the observed groundwater response to a flood event to perform a high resolution calibration of the subsurface hydrostratigraphy. Specifically, in this study we incorporate fining direction regularization (e.g., fining upwards/downwards) in a highly parameterized inversion driven by naturally occurring flood events.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Batlle-Aguilar et al (2015) used HGS to simulate the infiltration of surface water from a disconnected stream to groundwater for a river transect in South Australia; Alaghmand et al (2016) used HGS to investigate the potential use of artificial flooding as a short-term saline groundwater management technique along floodplains in arid and semi-arid environments; Xie et al (2016) of saline groundwater with surface water during stream events within an idealized river reach; and Schilling et al (2017) used HGS to investigate the impact of river bed clogging on surface water-groundwater interaction and the redistribution of water beneath disconnected streams. While several numerical modeling studies have been applied to specifically investigate surface watergroundwater interaction during flood events (Whiting and Pomeranets 1997;Chen et al 2006;Doble et al 2012a;Doble et al 2012b;Xie et al 2016;Liang et al 2018) these studies have not used the observed groundwater response to a flood event to perform a high resolution calibration of the subsurface hydrostratigraphy. Specifically, in this study we incorporate fining direction regularization (e.g., fining upwards/downwards) in a highly parameterized inversion driven by naturally occurring flood events.…”
Section: Introductionmentioning
confidence: 99%